2018
DOI: 10.15448/1980-8623.2018.2.27890
|View full text |Cite
|
Sign up to set email alerts
|

O convívio de adolescentes em medida socioeducativa de internação com a equipe técnica

Abstract: Este artigo está licenciado sob forma de uma licença Creative Commons Atribuição 4.0 Internacional, que permite uso irrestrito, distribuição e reprodução em qualquer meio, desde que a publicação original seja corretamente citada. http://creativecommons.org/licenses/by/4.0/deed.pt_BR Artigo originAl ISSN 1980-8623 ResumoO objetivo deste artigo é caracterizar o convívio de adolescentes em medida socioeducativa de internação com a equipe técnica, a partir da perspectiva dos adolescentes. Foram realizadas ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 11 publications
2
1
0
7
Order By: Relevance
“…Similar results were found by a study based in Porto Alegre (Coscioni, Farias, Garcia, Rosa, & Koller, 2018), which characterized coexistence of juvenile offenders with the technical team. Based on interviews with ten adolescents and also being grounded on BTHD, the research identified the local Judiciary and Executive Branch as exosystem elements that disfavored the establishment of proximal processes between adolescents and technicians.…”
Section: Technical Teamsupporting
confidence: 88%
“…Similar results were found by a study based in Porto Alegre (Coscioni, Farias, Garcia, Rosa, & Koller, 2018), which characterized coexistence of juvenile offenders with the technical team. Based on interviews with ten adolescents and also being grounded on BTHD, the research identified the local Judiciary and Executive Branch as exosystem elements that disfavored the establishment of proximal processes between adolescents and technicians.…”
Section: Technical Teamsupporting
confidence: 88%
“…The Judiciary Power also contributes to the precariousness of work, due to the accumulation of judicial demands that hinder the performance of pedagogical activities -either by overwork, or by institutional aspects that assign the role of evaluating adolescents to the technical staff. A similar state of precarious work was found in other Brazilian studies (Coscioni, Farias, et al, 2018;Oliveira & Assis, 1999;Souza & Costa, 2012), which leads to the understanding that this is a national reality.…”
Section: Technical Staffsupporting
confidence: 83%
“…In addition to the precarious investments in human and material resources, overwork undermined the quality of both functions: technical assistance and evaluation. Adolescents interviewed in Porto Alegre (Coscioni, Farias, et al, 2018) identified that the main function of the technical staff was to write reports submitted to the Judicial Power, which directly interfered with their interpersonal relations. In a study in the Federal District (Souza & Costa, 2012), the researcher observed attempts by the technical staff to conduct their duties in accordance with SINASE, which was hampered by the precariousness of human and material resources.…”
mentioning
confidence: 99%
“…Nesta categoria, foram agrupados os resultados dos artigos que apontam a escuta como a principal ferramenta de atuação do psicólogo, caracterizando uma contribuição específica da psicologia ao trabalho interdisciplinar. A escuta pode oferecer ao adolescente um lugar de protagonismo e reconhecimento, pois ele poderá construir uma narrativa pessoal sobre seus atos, seu passado, sua inserção no contexto socioeducativo e seus projetos para o futuro (Aragão, Margotto, & Batista, 2012;Capanema & Vorcaro, 2012;Coscioni, Farias, Rosa, & Koller, 2018;Ferrão, Santos & Dias, 2016;Guerra, Cunha, Costa, & Silva, 2014;Gurski & Strzykalski, 2018;Rosa & Cerutti, 2014;Siqueira & Tavares, 2013;Souza & Moreira, 2014).…”
Section: A Escuta Como Principal Ferramenta De Atuaçãounclassified
“…Com relação aos efeitos da escuta clínica, o estudo de Coscioni et al (2018) identificou que as intervenções de apoio psicológico contribuem para tranquilizar, acalmar, dar ânimo e suporte, além de ajudar os adolescentes a aliviar a pressão psicológica que sentiam durante a internação. Mais especificamente sobre a escuta das histórias dos adolescentes, identificou-se que os atendimentos permitiam reelaborar experiências passadas e projetar perspectivas futuras.…”
Section: A Escuta Como Principal Ferramenta De Atuaçãounclassified